Using models to advance medicine: mathematical modeling of post-myocardial infarction left ventricular remodeling. Issue 3 (17th February 2022) - Lafci Büyükkahraman, Mehtap; Sabine, Gavin K.; Kojouharov, Hristo V.; Chen-Charpentier, Benito M.; McMahan, Sara R.; Liao, Jun
Abstract: The heart is an organ with limited capacity for regeneration and repair. The irreversible cell death and corresponding diminished ability of the heart to repair after myocardial infarction (MI), is a leading cause of morbidity and mortality worldwide. In this paper, a new mathematical model is presented to study the left ventricular (LV) remodeling and associated events after MI. The model accurately describes and predicts the interactions among heart cells and the immune system post-MI in the absence of medical interventions. The resulting system of nonlinear ordinary differential equations is studied both analytically and numerically in order to demonstrate the functionality and performance of the new model. To the best of our knowledge, this model is the only one of its kind to consider and correctly apply all of the known factors in diseased heart LV modeling. This model has the potential to provide researchers with a predictive computational tool to better understand the MI pathology and develop various cell-based treatment options, with benefits of lowering the cost and reducing the development time.